Implementasi Merdeka Belajar dalam Peningkatan Literasi dan Numerasi Siswa - Shobri, Ach.; Masrukin; Sabri; Dianta Mustofa Kamal (Indo-MathEdu Intellectuals Journal, 2023)
This study evaluates the effectiveness of the "Merdeka Belajar" program launched by the Indonesian Ministry of Education and Culture in improving students' literacy and numeracy. A quantitative method with a quasi-experimental design was used to compare literacy and numeracy scores before and after program implementation in 10 senior high schools in East Java Province, with a total of 100 students as samples. The results showed significant improvements in literacy scores from 62.5 to 75.3 and numeracy scores from 58.7 to 72.1, with a p-value <0.01. Success factors included teachers' freedom in choosing teaching methods, principals' support and parents' involvement. However, challenges such as resource inequality between urban and rural schools and resistance to change remain. Recommendations for education policy include improving access and quality of education resources as well as continuous training for teachers and principals to ensure the sustainability and success of this program